Human papillomavirus types 6 and 11 mRNAs from genital condylomata acuminata. - Chow, L T (1987)
We have identified and mapped a number of RNA species of human papillomavirus types 6 and 11 from condylomata acuminata by the electron microscopic R-loop technique. Each of the early (E)- and late (L)-region open reading frames (ORFs) deduced from the DNA sequences was represented in one or more transcripts. In addition, RNA species that could encode the modulator of DNA replication and the repressor of transcription, functions recently identified in the genetically similar bovine papillomavirus type 1, were also detected. Some ORFs were 5' proximal in one or more transcripts, whereas others were not 5' proximal in any species, suggesting that internal initiation of translation might be required to gain access to these latter ORFs. Virtually all transcripts had their 5' ends located in the E region and were polyadenylated at one of two sites, i.e., at the end of the E region or at the end of the L region. The great majority of the RNAs were derived from the E region of the genome, with one species approximately 50 to 100 times more abundant than the others. For most of the RNAs, the 5' end mapped near nucleotide 700; minor populations had 5' ends near nucleotide 100 or 1200. By correlating our mapping data with the genomic DNA sequences as well as available RNA structures and cDNA sequences of several papillomaviruses, we predict a number of mRNA splice donor and acceptor sites and suggest that the papillomaviruses have sophisticated usage of ORFs through alternative promoters, mRNA splice sites, and polyadenylation sites.